2013
DOI: 10.1002/phar.1293
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Endogenous Adenosine in Ticagrelor-Induced Dyspnea

Abstract: Ticagrelor, a recently approved platelet antagonist indicated for the reduction of thrombotic cardiovascular events in patients with acute coronary syndrome (ACS), has been reported to cause dyspnea in more than 13% of patients. Dyspnea is not a clinically relevant adverse event with other medications indicated for ACS. One suggested mechanism of ticagrelor-induced dyspnea involves an increase in systemic adenosine concentrations through adenosine deaminase inhibition. Dyspnea, a subjective finding resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It may be that ticagrelor causes an increase in the endogenous adenosine concentration [46, 47] and the inhibition of P2Y 12 on sensory neurons [48]. …”
Section: Discussionmentioning
confidence: 99%
“…It may be that ticagrelor causes an increase in the endogenous adenosine concentration [46, 47] and the inhibition of P2Y 12 on sensory neurons [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Ticagrelor inhibits platelet activity via P2Y 12 receptor inhibition and also via adenosine [ 35 ]. A potential mechanism of ticagrelor-induced dyspnoea involves increased endogenous levels of adenosine [ 36 ]. Adenosine can induce dyspnoea in normal [ 37 ] and asthmatic [ 38 ] subjects.…”
Section: Ticagrelor Pharmacokinetic Profilementioning
confidence: 99%
“…Various side effects have been reported for both clopidogrel (bleeding, liver and bone injury, enhanced lipopolysaccharide-induced inflammation) [365,366] and ticagrelor (bleeding, dyspnoea) [367]. In more recent reports, it was suggested that there may be a role for endogenous adenosine in ticagrelor-induced dyspnoea [368,369].…”
Section: Thrombosismentioning
confidence: 99%